Images of Russians in Legends and Modern Stories of Indigenous Peoples of Yakutia - O. I. Charina (Научный диалог, 2018)
The reflection of the image of the Russian in aboriginal legends and stories on the territory of Yakutia for a long period is considered. Data on the composition of ethnic groups are given in the percentage to the entire population of the Northern regions, where indigenous peoples live (Chukchi, Evenks, Yukagirs), as evidenced by the 2010 census. The research urgency is caused by the fact that the image of the Russian in the oral prose of the indigenous peoples of the North was not considered in the dynamics. Text records made in the region during expeditions are used. Comparison with the texts of the prose works fixed from other folklore tellers - indigenous peoples of border lands. The novelty of the study is to compare records of different years: both early legends and family stories of the Chukchi, Evenks, Evens, Yukagirs and Yakuts, which were recorded in the first years of fixing folklore, and texts recorded relatively recently. The author proves that the image of the Russian in non-fairy-tale prose of the peoples of Yakutia was changing - from the mythological image of the alien to the modern character of the autobiographical stories of the beginning of the 21st century, intermarried with the Yakuts or being a steward of natural resources.